Building modernity a century of Philippine architecture and allied arts (Manila National Commission for Culture and Arts ; MOFA and Art Studies Foundation, 2008)
The landmark exhibit Building Modernity was first opened on Feb. 7, 2007 until Sept. 2007 at the Museum of the Filipino People as part of the Ani ng Sining Philippine Arts Festival 2007. The exhibit featured archival photographs, paintings, vintage graphics, blueprints, building components, building ornaments and related artifacts that highlight the various stylistic tendencies, movements, ideologies and technologies that molded the twentieth century architecture culture in the Philippines. This interactive multi-media CDROM endeavors to document the essence and message of the exhibit by compiling the complete catalogue of images and texts displayed at the museum.--containder.
CDROM.
Gerand Lico, Curator ; Edson Cabalfin, project director.
Keywords: Architecture -- Philippines